EMPOWERMENT OF OLDER PEOPLE TO PARTICIPATE IN EDUCATIONAL ACTIVITIES - Zemaitaityte, Irena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The article examines the empowerment of older adults to participate in educational activities in order to remain active members of the society. Empowerment is defined as the activation of the member to act on the basis of inner and outer resources. The growing number of older people in the society prompt to constantly review and adjust the resources of the society in the area of economy, education and health care to the new needs. Therefore, in order that older people would feel a fulfilling quality of life, it is necessary to promote them to be active, underpin social roles, provide them possibilities to engage in volunteering, educational, cultural activity and learn new things.